2015
DOI: 10.1007/s00280-015-2829-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for newly diagnosed patients with acute myeloid leukemia dosed on actual or adjusted body weight

Abstract: Purpose Data from solid tumor malignancies suggest that actual body weight (ABW) dosing improves overall outcomes. There is the potential to compromise efficacy when chemotherapy dosages are reduced, but the impact of dose adjustment on clinical response and toxicity in hematologic malignancies is unknown. The purpose of this study was to evaluate the outcomes of utilizing a percent of ABW for acute myeloid leukemia (AML) induction chemotherapy dosing. Methods This retrospective, single-center study included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Crysandt et al and Cahu et al 33,34 retrospectively analysed data from the prospective clinical trials AML2003 and GOELAMS 2001 including younger adults (≤60 years) with higher proportions of favourable cytogenetic risk, and found either a univariate association to inferior survival 33 or a trend towards inferior survival but no differences in event‐free survival 34 . Other studies included older patients (>60 years) mostly from single institution experiences have not been able to associate DR or dose capping to inferior survival 35–39 . However, none of the afore‐mentioned studies adjust for known powerful covariates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Crysandt et al and Cahu et al 33,34 retrospectively analysed data from the prospective clinical trials AML2003 and GOELAMS 2001 including younger adults (≤60 years) with higher proportions of favourable cytogenetic risk, and found either a univariate association to inferior survival 33 or a trend towards inferior survival but no differences in event‐free survival 34 . Other studies included older patients (>60 years) mostly from single institution experiences have not been able to associate DR or dose capping to inferior survival 35–39 . However, none of the afore‐mentioned studies adjust for known powerful covariates.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Several other studies have assessed this question and the results are conflicting; where some find a negative survival effect of DR or dose capping, 33,34 others find no effect or better outcomes in overweight receiving DR or dose capping. [35][36][37][38][39] Notable differences between studies are study population, cytogenetic risk, and age. Crysandt et al and Cahu et al 33,34 retrospectively analysed data from the prospective clinical trials AML2003 and GOELAMS 2001 including younger adults (≤60 years) with higher proportions of favourable cytogenetic risk, and found either a univariate association to inferior survival 33 or a trend towards inferior survival but no differences in event-free survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have suggested that obesity is a risk factor associated with AML. [1][2][3] Classically, karyotyping has formed a powerful independent prognostic indicator in this group of diseases. 4,5 It serves to identify biologically distinct subsets of disease and has been widely used to provide the framework for risk-adapted treatment approaches.…”
Section: Introductionmentioning
confidence: 99%